Faire lire un recit de fiction complet : Proposition d’une procédure visant à former l’amateur éclairé - Dumortier, Jean-Louis (Linguarum Arena, 2018)
The article addresses all school teachers as well as their trainers. It is divided into two parts. In the first part the author assumes the general view that students tend to dislike reading fiction nowadays, and echoes a doubt that others have expressed before him: that perhaps the type of school reading approach is not very similar to that of the amateur. Between the “primary” reading of the latter and the “secondary” reading of the specialist, this paper proposes a middle path that corresponds to the reading of what is called here the “enlightened amateur”. What characterizes this approach is the consideration of the escompte d’agrément of the amateur and the attention paid to potential factors of the latter, inherent in the work of fiction. In the second part, the author proposes a procedure, adaptable according to the level and teaching method, which breaks with the practice which can be summarised by the formula “Read first, and we can talk about it later”. According to this procedure, in five or six stages, the teacher accompanies and guides the students in their journey of discovery through the chosen text